Students’ Management to Increase the Character and Achievement in MAN 2 Banjarnegara - Akhmad, Sidik Wibowo (International Conference of Moslem Society, 2018)
The purpose of this study was to describe the students’ management in increasing the character and achievement in MAN 2 Banjarnegara including: (1) the enrollment process of new students, (2) guiding students through discipline, noble character building, academic and non-academic achievement, and (3) the impact of character building and the achievement for students MAN 2 Banjarnegara. This research implemented descriptive qualitative approach. The data collection techniques were in-depth interview, observation, and documentation study. The validity of the data used three criteria; namely credibility, dependability, and conformability. The findings of this study were: The first, the enrollment process of the new students was made a breakthrough during the registration of academic and non-academic achievement of scholarships, the selection process was conducted through the value of official learning reports, certificate of championship/achievement, academic potential test and non-academic, and also the skill test. For the students who passed the selection process were supposed to sign the achievement contract during the learning process at MAN 2 Banjarnegara. The second, the character building was done by the concept of habituation and activities program that were integrated in curricular and extracurricular activities. The third, students who joined the academic and non-academic achievement programs at MAN 2 Banjarnegara had strong motivation, spirit of competition to achieve higher achievement and more focus on self-development and they could anticipate the usage of spare time for positive things/activities.